Pendidikan Agama Islam dalam Menumbuhkan Kepribadian Muslim Peserta Didik Boarding School - Huda, Aris Syaiful (Pascasarjana IAIN Kudus, 2020)
Artikel ini bertujuan untuk mengetahui makna pendidikan agama, makna kepribadian muslim peserta didik dan mengetahui pengalaman dan makna pendidikan agama Islam dalam menumbuhkan kepribadian muslim peserta didik melalui program boarding school di SMK Negeri Jawa Tengah di Pati. Penelitian ini merupakan penelitian lapangan dengan pendekatan kualitatif kategori fenomenologi. Hasil penelitiannya menunjukkan ada 3 klaster tema dari para partisipan. Hasilnya adalah esensi pengalaman digali dari makna yang dilekatkan oleh partisipan atas pengalaman mereka yang mencakup makna tentang kegiatan belajar mengajar pendidikan agama Islam yang menyenangkan, makna kepribadian muslim dengan bertambahnya Iman semakin kuat, dan makna pendidikan agama Islam dalam menumbuhkan kepribadian muslim peserta didik melalui program boarding school dengan selalu beramal shaleh.The purpose of this study was to determine the meaning of religious education, the meaning of Muslim personality of students and to know the experience and meaning of Islamic religious education in fostering Muslim personality of students through the boarding school program at SMK Negeri Jawa Tengah in Pati. This research is a field research with a qualitative approach to the phenomenological category. The results of his research showed that there were 3 theme clusters of the participants. The result is that the essence of experience is extracted from the meaning attached by the participants to their experience which includes the meaning of fun Islamic religious education teaching and learning activities, the meaning of Muslim personality with increasing faith is getting stronger, and the meaning of Islamic religious education in fostering the Muslim personality of students through the boarding program. school by always doing good deeds.